High drug payload nanoparticles formed from dexamethasone-peptide conjugates for the treatment of endotoxin-induced uveitis in rabbit - Yu X (Dove Medical Press, 2019)
Xinxin Yu, Renshu Zhang, Lei Lei, Qianqian Song, Xingyi Li Institute of Biomedical Engineering, School of Ophthalmology and Optometry and Eye Hospital, Wenzhou Medical University, Wenzhou 325027, People’s Republic of China Purpose: To develop and demonstrate the effectiveness of a novel dexamethasone (Dex) nanoformulation for treating uveitis. Materials and methods: We designed and screened a dexamethasone-peptide conjugate (Dex-SA-FFFE), formed via a biodegradable ester bond linkage, that could spontaneously form high drug payload nanoparticles in aqueous solution for treating uveitis. Results: An in vitro release study indicated that Dex and Dex-SA-FFFE sustainably released from Dex-SA-FFFE nanoparticles over a 48 h study period. Meanwhile, the formed Dex-SA-FFFE nanoparticles hardly caused cytotoxicity in human corneal epithelial cell at drug concentrations up to 1 mM after 24 h of incubation but reduced cell viability after 48 h and 72 h of incubation. An in vitro anti-inflammatory efficacy assay showed that the Dex-SA-FFFE nanoparticles exhibited a comparable anti-inflammatory efficacy to that of Dex in lipopolysaccharide (LPS)-activated RAW264.7 macrophages via significant decreases in the secretion of various pro-inflammatory cytokines (e.g., nitric oxide, tumor necrosis factor-α, interleukin-6). Topical instillation of Dex-SA-FFFE nanoparticles showed good ocular tolerance without causing changes in corneal thickness and intraocular pressure during the entire study period. Furthermore, topical instillation of Dex-SA-FFFE nanoparticles displayed a comparable in vivo therapeutic efficacy to that of dexamethasone sodium phosphate (Dexp) aqueous solutions in an endotoxin-induced uveitis (EIU) rabbit model. Conclusion: Based on these results, it is reasonable to believe that the proposed Dex-SA-FFFE nanoparticles might have great application for the treatment of anterior uveitis. Keywords: drug-peptide conjugate, self-assembly, ocular inflammation, in vivo, nanoparticle